Топологія в тривимірній графіці - Шевченко, В. Ю. (ХНУРЕ, 2025)
This paper describes the topology in 3D graphics, focusing on the structure and organization of vertices, edges, and faces within a 3D model. The study highlights the importance of baking normal maps to transfer details from high poly to low-poly models, optimizing performance without compromising visual quality. Topology principles vary depending on the intended use, making models for gaming, 3D printing, and visual rendering distinct and noninterchangeable. Understanding these principles is important for achieving high quality, real-time visualizations efficiency.
Keywords: топологія; тривимірна графіка